The Crown’s duty to consult with First Nations - Chartier, Mélanie (Allard Research Commons, 2009)
The Crown has fiduciary obligations to First Nations and must act in consequence. One of this consequence is that the Crown has a duty to consult with aboriginal peoples when it infringes aboriginal or treaty right. The thesis deals with the principles related to the Crown's duty to consult with First Nations. I elaborate on principles established by the courts and also on questions that remain unanswered to date. Those questions include when, how and with whom the consultation should be done. I also examine the situation in New Zealand, where the consultation process is a little more advanced than here in Canada and compare the principles elaborated by New Zealand courts with those existing in Canada. From the New Zealand experience, I suggest consultation guidelines to be used in Canada by the Crown and its representatives.